Let's simplify both sides of the equation step by step.
Left Side:
For the left side, we have: \[ 2(x - 5) \]
Applying the Distributive Property: \[ 2 \cdot x - 2 \cdot 5 = 2x - 10 \]
Right Side:
For the right side, we have: \[ 9 - 3x + 6 + 8 + 3x + 7 \]
Now, let's combine like terms. First, let's separate the constants and the \(x\) terms:
- Constants: \(9 + 6 + 8 + 7\)
- \(x\) terms: \(-3x + 3x\)
Calculating the constants: \[ 9 + 6 = 15 \] \[ 15 + 8 = 23 \] \[ 23 + 7 = 30 \]
Now for the \(x\) terms: \[-3x + 3x = 0\]
Putting it all together, the right side simplifies to: \[ 30 \]
Summary:
- The left side simplifies to: \(2x - 10\)
- The right side simplifies to: \(30\)
So after simplification, the equation looks like: \[ 2x - 10 = 30 \]